Acute Asthma Models to Ovalbumin in the Mouse. Issue 1 (1st March 2013) - Daubeuf, François; Frossard, Nelly
Abstract: Human asthma is defined as a chronic inflammatory disease of the airways. Animal models are required to study asthma pathophysiology and identify and/or evaluate new therapeutic strategies. Several models of asthma have been developed in mice to mimic asthma symptoms, and can be divided in two groups as acute and chronic models. They are characterized by airway hyperresponsiveness (AHR), inflammation, and remodeling. Several experimental procedures have been implemented, the one mostly used being acute asthma models to ovalbumin. It comprises a sensitization step in the presence of aluminum hydroxide as an adjuvant, and a second step where mice are challenged with the allergen introduced directly into the airways to induce the modeled asthma features. This article describes procedures to efficiently and reproducibly obtain acute asthma features in mice, with ovalbumin as the allergen, which allow group comparisons and/or assessment of the activity of drug candidates. Curr. Protoc. Mouse Biol . 3:31‐37 © 2013 by John Wiley & Sons, Inc.